Fermentation and the Ethnobiology of Microbial Entanglement - Andrew Flachs; Joseph D. Orkin (Ethnobiology Letters, 2019)
Fermentation preserves and transforms foods through autochthonous or introduced microorganisms. Fermentation is of special interest to ethnobiologists because it relies on place- and practice-based knowledge, local flora and microbial taxa, is sensitive to cultural and ecological conditions, and illuminates the interactions through which communities shape and are shaped by the world around them. In this short topical review, we discuss recent anthropological and ethnobiological research into fermentation, arguing that this topic deserves further attention during the current moment of microbial interest across social and natural sciences. We present a typology of scholarship on human-microbial relationships that delineates three intellectual camps in this literature: neo-cultural ecology, microbiopolitics, and the environmental humanities. In light of biomedical and scientific attention to microbes—not only as threats but also as complex and beneficial actors in our lives—it is crucial to understand how socioecological practices including growing, preparing, and consuming fermented foods sustain microbial communities, heritage foodways, and human wellbeing.